PREPARATION AND TENSILE PROPERTY OF 3D POROUS LATTICE STRUCTURE FOR SKIN TISSUE ENGINEERING SCAFFOLDS - FANG Chuang; JI XiaoGang; WANG Wei (Jixie qiangdu)
Digital light process(DLP)forming method has the high forming speed and accuracy characteristics,and can be better used for the preparation of tiny size structures.Therefore,in this study,a new 3D porous lattice structure obtained by artificial topology⁃optimized square lattice as a single cell and spatial 3D equally spaced array of the single cell was designed.Then a flexible and elastic photosensitive resin by using DLP forming method for preparation experiments was carried out.The influence of DLP printing on the formation of the lattice structure and the forming effect were investigated.The tensile mechanical properties of all samples of complete structure without siltation were studied.The results show that the new porous structure prepared by DLP printing has clear internal pores and good connectivity in which the porosity reached more than 80%,and the elongation at break is also above 856%,among which the tensile toughness of lattice structure 3 is the largest and its comprehensive tensile properties are the best.The structure can be widely used in skin tissue engineering scaffolds,flexible electrodes,fragile product clamping fixtures,etc.